In ovo Inoculation of Bacillus subtilis and Raffinose Affects Growth Performance, Cecal Microbiota, Volatile Fatty Acid, Ileal Morphology and Gene Expression, and Sustainability of Broiler Chickens (Gallus gallus) - Shehata, Abdelrazeq M.; Paswan, Vinod K.; Attia, Youssef A.; Abougabal, Mohammed Sh.; Khamis, Tarek; Alqosaibi, Amany I.; Alnamshan, Mashael M.; Elmazoudy, Reda; Abaza, Mohamed A.; Salama, Ehab A. A.; El-Saadony, Mohamed T.; Saad, Ahmed M.; et al. (Frontiers in Nutrition, 2022)
Banning antibiotic growth promoters has negatively impacted poultry production and sustainability which led to exploring efficient alternatives such as probiotics, probiotics, and synbiotics. Effect of in ovo injection of Bacillus subtilis, raffinose, and their synbiotics on growth performance, cecal microbial population and volatile fatty acid concentration, ileal histomorphology, and ileal gene expression was investigated in broilers (Gallus gallus) raised for 21 d. On h 300 of incubation, a total of 1,500 embryonated eggs were equally allotted into 10 groups. The first was the non-injected (NC) and remaining in ovo injected with sterile distilled water (PC), B. subtilis 4x105and 4x106 CFU (BS1 and BS2), Raffinose 2 and 3 mg (R1 and R2), B. subtilis 4x105 CFU + raffinose 2 mg (BS1R1), B. subtilis 4x105 CFU + raffinose 3 mg (BS1R2), B. subtilis 4x106 CFU + raffinose 2 mg (BS2R1), B. subtilis 4x106 CFU + raffinose 3 mg (BS2R2). At hatch, 60 chicks from each group were randomly chosen, divided into groups of 6 replicates (10 birds/replicates), and fed a corn-soybean-based diet. In ovo inoculation of B. subtilis and raffinose alone or combinations significantly improved body weight, feed intake, and feed conversion ratio of 21-day-old broilers compared to NC. Cecal concentrations of butyric, pentanoic, propionic, and isobutyric acid were significantly elevated in R1, R2, BS2R1, and BS2R2, while isovaleric and acetic acids were significantly increased in R1 and BS2R1 compared to NC. Cecal microbial population was significantly altered in treated groups. Ileal villus height was increased (P<0.001) in BS1, R2, and BS2R2 compared to NC. The mRNA expression of mucin-2 was up-regulated (P<0.05) in synbiotic groups except for BS1R1. VEGF expression was increased (P<0.05) in BS2, R1, BS1R1, and BS1R2 compared to NC. SGLT-1 expression was up-regulated (P<0.05) in all treated birds except those of R1 group compared to NC. The mRNA expressions of IL-2 and TLR-4 were down-regulated (P<0.05) in BS2 and R1 for IL-2 and BS1R1 and BS2R2 for TLR-4. It was concluded that in ovo B. subtilis, raffinose, and synbiotics positively affected growth performance, cecal microflora, gut health, immune responses, and thus the sustainability of production in 21-day-old broilers.